Analisis Macam-Macam Istifham dan Maknanya dalam Surat Al-Baqarah Ayat 1-75 : Studi Analisis Balaghah - Hani’atul Mabruroh; Adinda Zakiya Yasmin; Nikianaku Seisagita Ardya; Zuhriyyatul Athiroh (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
The Qur'an, as the greatest miracle revealed to the Prophet Muhammad peace be upon him, possesses a linguistic excellence unmatched by Arab writers, both during and after the revelation. The beauty of its sentence structure, rhetorical power, and the depth of meaning in each sentence make the Qur'an an authentic proof of the Prophet's prophethood. Among the prominent linguistic characteristics in the Qur'an is the use of the istifham style interrogative sentences, which in the science of balaghah is included in the branch of ma'ani. Interrogative sentences in the Qur'an are not always intended to ask for answers, but often contain rhetorical intent that strengthens arguments, raises awareness, or even touches the psychological aspects of the reader.